Digital technology administrative penalties and green technology innovation: Evidence from China - Hong Li; Xiaohui Chen (Heliyon)
In digital economy era, digital technology is a key force to promote green technological innovation (GTI). Digital technology administrative penalties (DTAP) are an important means to regulate the development of digital technology enterprises, but its ability to effectively guide digital technology enterprises to better serve GTI remains to be further examined. DTAP sends signals to physical enterprises, financial enterprises, and individuals, thereby affecting the allocation of resources, such as technology, talent, and funds. Green technology innovation requires support from these resources, raising the question of how DTAP may affect GTI. This study proposes hypotheses based on signal theory and uses urban data from China from 2008 to 2020 to empirically test the impact of DTAP on GTI. The research findings indicate that DTAP is conducive to improving regional GTI, and DTAP facilitates GTI by fostering digital industrialization and financial technology development. The heterogeneity analysis reveals that the DTAP has a stronger promotion effect on the GTI in municipalities and low-carbon pilot cities. Our research is meaningful and can serve as a reference for other developing countries to standardize administrative supervision of the digital economy and promote the green economic transformation.